The tumor suppressor FBXO31 preserves genomic integrity by regulating DNA replication and segregation through precise control of cyclin A levels - Dutta, Parul (J Biol Chem, 2019)
F-box protein 31 (FBXO31) is a reported putative tumor suppressor, and its inactivation due to loss of heterozygosity is associated with cancers of different origins. An emerging body of literature has documented FBXO31's role in preserving genome integrity following DNA damage and in the cell cycle. However, knowledge regarding the role of FBXO31 during normal cell-cycle progression is restricted to its functions during the G(2)/M phase. Interestingly, FBXO31 levels remain high even during the early G(1) phase, a crucial stage for preparing the cells for DNA replication. Therefore, we sought to investigate the functions of FBXO31 during the G(1) phase of the cell cycle. Here, using flow cytometric, biochemical, and immunofluorescence techniques, we show that FBXO31 is essential for maintaining optimum expression of the cell-cycle protein cyclin A for efficient cell-cycle progression. Stable FBXO31 knockdown led to atypical accumulation of cyclin A during the G(1) phase, driving premature DNA replication and compromised loading of the minichromosome maintenance complex, resulting in replication from fewer origins and DNA double-strand breaks. Because of these inherent defects in replication, FBXO31-knockdown cells were hypersensitive to replication stress-inducing agents and displayed pronounced genomic instability. Upon entering mitosis, the cells defective in DNA replication exhibited a delay in the prometaphase–to–metaphase transition and anaphase defects such as lagging and bridging chromosomes. In conclusion, our findings establish that FBXO31 plays a pivotal role in preserving genomic integrity by maintaining low cyclin A levels during the G(1) phase for faithful genome duplication and segregation.